New 99mTc-Labeled Digitoxigenin Derivative for Cancer Cell Identification - Munkert, Jennifer; Gomes, Eliza R.; Marostica, Lucas L.; Cota, Betânia B.; Lopes, Cristina L.M.; Andrade, Saulo F.; Filho, José D.De Souza; Alves, Ricardo J.; Oliveira, Monica C.; Braga, Fernão C.; Simões, Cláudia M.O.; Pádua, Rodrigo M.; et al. (ACS Omega, 2019)
In recent years, cardiac glycosides (CGs) have been investigated as potential antiviral and anticancer drugs. Digitoxigenin (DIG) and other CGs have been shown to bind and inhibit Na+/K+-adenosinetriphosphatase (ATPase). Tumor cells show a higher expression rate of the Na+/K+-ATPase protein or a stronger affinity towards the binding of CGs and are therefore more prone to CGs than non-tumor cells. Cancer imaging techniques using radiotracers targeted at specific receptors have yielded successful results. Technetium-99m (99mTc) is one of the radionuclides of choice to radiolabel pharmaceuticals because of its favorable physical and chemical properties along with reasonable costs. Herein, we describe a new Na+/K+-ATPase targeting radiotracer consisting of digitoxigenin and diethylenetriaminepentaacetic acid (DTPA), a bifunctional chelating ligand used to prepare 99mTc-labeled complexes, and its evaluation as an imaging probe. We report the synthesis and characterization of the radiolabeled compound including stability tests, blood clearance, and biodistribution in healthy mice. Additionally, we investigated the binding of the compound to A549 human non-small-cell lung cancer cells and the inhibition of the Na+/K+-ATPase by the labeled compound in vitro. The 99mTc-labeled DTPA-digitoxigenin (99mTc-DTPA-DIG) compound displayed high stability in vitro and in vivo, a fast renal excretion, and a specific binding towards A549 cancer cells in comparison to non-tumor cells. Therefore, 99mTc-DTPA-DIG could potentially be used for non-invasive visualization of tumor lesions by means of scintigraphic imaging.
CRIS-Team Scopus Importer:2019-12-31